A NEW SPECIES OF ANATHALLIS (ORCHIDACEAE: PLEUROTHALLIDINAE) FROM BRAZIL - A. L. V. Toscano De Brito (Lankesteriana International Journal on Orchidology, 2018)
Anathallis luteola is newly described and illustrated from the state of Bahia, northeast Brazil. It is similar to A. guarujaensis from which it can be distinguished by the smaller flowers, the successive two- flowered raceme, and shape of its floral segments. A note on the latter species is also provided.